Nominal phrases with the word "coup" and their translation into Spanish - Barceló Martínez, Tanagua (Estudios de Traducción, 2016)
The existence of phraseological units (PU) constitutes an enrichment at the very heart of any language. With regard to translation, however, they usually create barriers both in the comprehension phase and in the rewriting phase (in the search for the suitable equivalents). In the case of the French- Spanish linguistic combination, the proximity of both languages facilitates comprehension on some occasions, but, for its part, it also favours phenomena such as false friends in the translation process. This paper aims to present a broad study derived from the classification and analysis of French expressions containing the term coup and their translation into Spanish. To this end, we shall: a) justify the choice of the subject matter; b) expose the methodology used; c) define what a phraseological unit is, and its different types; and d) illustrate, with the use of some examples, part of our study, namely the section related to nominal locutions. Finally, the most significant conclusions drawn from this study will be outlined.
Keywords: phraseological unit; nominal locutions with coup; French-Spanish.